Ion tracks in silicon formed by much lower energy deposition than the track formation threshold - H. Amekura; M. Toulemonde; K. Narumi; R. Li; A. Chiba; Y. Hirano; K. Yamada; S. Yamamoto; N. Ishikawa; N. Okubo; Y. Saitoh (Scientific Reports, 2021)
Abstract Damaged regions of cylindrical shapes called ion tracks, typically in nano-meters wide and tens micro-meters long, are formed along the ion trajectories in many insulators, when high energy ions in the electronic stopping regime are injected. In most cases, the ion tracks were assumed as consequences of dense electronic energy deposition from the high energy ions, except some cases where the synergy effect with the nuclear energy deposition plays an important role. In crystalline Si (c-Si), no tracks have been observed with any monomer ions up to GeV. Tracks are formed in c-Si under 40 MeV fullerene (C60) cluster ion irradiation, which provides much higher energy deposition than monomer ions. The track diameter decreases with decreasing the ion energy until they disappear at an extrapolated value of ~ 17 MeV. However, here we report the track formation of 10 nm in diameter under C60 ion irradiation of 6 MeV, i.e., much lower than the extrapolated threshold. The diameters of 10 nm were comparable to those under 40 MeV C60 irradiation. Furthermore, the tracks formed by 6 MeV C60 irradiation consisted of damaged crystalline, while those formed by 40 MeV C60 irradiation were amorphous. The track formation was observed down to 1 MeV and probably lower with decreasing the track diameters. The track lengths were much shorter than those expected from the drop of S e below the threshold. These track formations at such low energies cannot be explained by the conventional purely electronic energy deposition mechanism, indicating another origin, e.g., the synergy effect between the electronic and nuclear energy depositions, or dual transitions of transient melting and boiling.